Las redes sociales y su influencia en la comunicación de los estudiantes de tercer año de bachillerato de la Unidad Educativa “José Rodríguez Labandera”, del Cantón Quevedo - Cobo Holguin, Exandra Maoly (2017)
Young people today are the so-called children of the Net generation. They grew up with the internet at their fingertips. They dominate almost everything on the Internet and are always '' onlin '' in social networks that multiply every year. Twitter, Tumblr, Facebook, Instagram, Viber, WhatsApp are in their languages. In the city of Quevedo, more than half of the population use social networks, mainly in schools, students' use of social networks and their influence on their communication becomes a serious problem because of Which establishes the research: Social networks and their influence in the communication of the students of Third Year of Bachillerato of the Educational Unit José Rodríguez Labandera, Canton Quevedo, 2017; Where objectives were established such as: How can social networks attract students' interest in influencing correct communication? In what way, the application of measures by the authorities on social networks will achieve a better Communication ?, What kind of influence, through the implementation of an alternative model of social network control will improve student communication ?. It was possible to have the opinion of the parents and teachers in the survey. For this reason, the present research aims to analyze the influence of social networks in the communication of students, in order to achieve great benefits, to improve their academic performance through the use of educational programs and the use of networks Social services for academic purposes; Preliminary it is observed that social networks positively influence the communication of the students of the Third Year of Bachillerato of the Educational Unit "José Rodríguez Labandera", Canton Quevedo, 2017